Deconvolution of TEOS/TEVS Xerogel by Single or Dual Organic Catalyst Addition - Adi Darmawan; Isna Syauqiah; Anna Sumardi; Muthia Elma; Aptar Eka Lestari; Zaini Lambri Assyaifi; Erdina Lulu Atika Rampun; Yanti Mawaddah; Linda Suci Wati (Syarif Hidayatullah State Islamic University, 2020)
Currently, xerogel has been applied as a filtration material, especially in membrane desalination. However, the xerogel matrix structure for desalination have to be designed properly in order to allow rejection of salt and obtain good hydro-stability, thus, silica precursor in the form of TEOS (tetraethyl orthosilicate)/TEVS (triethoxy vinyl silane) and organic acid catalyst are suitable material for fabrication. The aim of this study is therefore to fabricate and perform deconvolution of TEOS/TEVS xerogel by adding single or dual catalyst, using FTIR (Fourier-transform Infrared Spectroscopy) and Fityk software. The xerogel was fabricated by dried silica sol and calcined using RTP technique (rapid thermal processing) at 450 °C. Prior to this fabrication, the silica sol was synthesized by sol gel method, using a mixture of silica precursor TEOS/TEVS, ethanol solvent, and varied addition of single catalyst (citric acid) as well as dual catalyst (citric acid + ammonia) for 2 hours, at 50 °C. Subsequently, the xerogel was characterized by FTIR and the deconvolution was obtained through Gaussian approach, with Fityk software. All TEOS/TEVS xerogel samples indicated existence of silanol (Si-OH), siloxane (Si-O-Si) and silica-carbon (Si-C) functional groups. The xerogel deconvolution of TEOS/TEVS using single catalyst exhibit a peak area ratio of Si-OH/Si-O-Si, and this is similar to the dual catalyst counterpart of 0.24 (unit area) and 1.86 (unit area), for Si-C area ratio. This shows the addition of single catalyst was enough to produce deconvolution in TEOS/TEVS xerogel, dominated by siloxane functional group and carbon bonds with the ability to enhance membrane material hydro-stability’s fabrication.